PELATIHAN ALAT TIUP BRASS MARCHING BAND DI PONDOK PESANTREN DAAR EL-QOLAM - Azmi, Najwa; Andriyanto, Raden Mas Aditya; Ichwan, Clemy Ikasari (Jurnal Penelitian Musik, 2023)
Abstract: The purpose of this study was to determine the training process for brass instruments in marching bands at the Daar El-Qolam Islamic Boarding School, Banten. The research method used is descriptive qualitative method. Data collection techniques used in this study were direct observation, interviews with sources and experts, as well as written sources. The data analysis technique used in this study is by means of data reduction, data presentation and drawing conclusions. The results of this study indicate that the training of brass instruments in marching bands at the Modern Islamic Boarding School Daar El-Qolam Banten has a routine training schedule of three times a week. There are 4 types of brass instruments used, namely trumpet, mellophone, baritone and tuba. The determination of the material provided is adjusted for new brass members and old brass members. The training methods used by the trainers are the lecture method, the demonstration method, the drill method and the imitation method. Marching band activities have very good benefits, including being able to increase the confidence of the members, that with this activity they are able to appear in front of many people, this confidence will be very beneficial for their future life in facing various challenges and obstacles in their life. A marching band member will also have loyalty, good leadership, achievement and also have good teamwork.